fy+3=gx+-15

Simple and best practice solution for fy+3=gx+-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for fy+3=gx+-15 equation:


Simplifying
fy + 3 = gx + -15

Reorder the terms:
3 + fy = gx + -15

Reorder the terms:
3 + fy = -15 + gx

Solving
3 + fy = -15 + gx

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + fy = -15 + -3 + gx

Combine like terms: 3 + -3 = 0
0 + fy = -15 + -3 + gx
fy = -15 + -3 + gx

Combine like terms: -15 + -3 = -18
fy = -18 + gx

Divide each side by 'y'.
f = -18y-1 + gxy-1

Simplifying
f = -18y-1 + gxy-1

Reorder the terms:
f = gxy-1 + -18y-1

See similar equations:

| 10x^3+6x^2=0 | | -9x-40= | | 3x-2/3(2x-1)=4 | | 6+3n= | | 36x^4-81x^7=0 | | -6x-4(7x+13)=186 | | 20/6x-7/6=9/6 | | 0.18=x^12 | | 4=15r-7 | | 6(x-3)=-2(x-7) | | 6x+18=10x-6 | | 47=5x-(7-4x) | | 7x+3y=50000 | | -(3x+5)=2x | | -d+4e=-3 | | -6(x-6)=3(0+x) | | 0.5=0.4 | | R+2-3=4 | | x+(x-20)=78 | | 11x-7(-4+2x)=-14 | | 7x+3=56 | | -4x^2-5.5x+5=0 | | -5x-4(-3x+15)=3 | | -6(-v-3y+4)= | | 2x^2-4x+4=25 | | 0.8x-4=1.5x+0.2 | | 48.15/45 | | 0.8x-4=1.5+0.2 | | f(x)=x^4+8x^2-12 | | x^2-2x=10.5 | | 3x+4(-4x+16)=8 | | 3x+10=2x+x+18 |

Equations solver categories